2011
DOI: 10.1007/s10750-011-0699-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and the genetic structure of the land-locked freshwater prawn Macrobrachium asperulum (Crustacea: Decapoda: Palaemonidae) in Taiwan

Abstract: Macrobrachium asperulum is a landlocked macroinvertebrate species of freshwater prawn, which inhabits a wide range of freshwater bodies and has an abundant pan-island distribution in Taiwan. In this study, we used mitochondrial (mt)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
4
19
2
Order By: Relevance
“…De Jong et al (2011) attributed these subtle differences to geographical isolation. This would be in line with the reports of many authors, which have reported the genetic effects of human introduction on some freshwater animals (Shih et al 2004;Wang et al 2004;Liu et al 2011).…”
supporting
confidence: 92%
“…De Jong et al (2011) attributed these subtle differences to geographical isolation. This would be in line with the reports of many authors, which have reported the genetic effects of human introduction on some freshwater animals (Shih et al 2004;Wang et al 2004;Liu et al 2011).…”
supporting
confidence: 92%
“…This outcome is different from the outcomes that were often found of a high degree of phylogeographically related genetic structure [11, 42, 47, 48, 49, 50, 51, 52, 53, 54]. This might be because the expansion time for lineage A (209,533 yrs ago) or lineage B (49,248 yrs ago) were too short to accumulate enough genetic variation and form geographically unique clade [55, 56, 57].…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have shown that several factors, such as glacial events and mountain-island isolations, promoted the diversity of endemic species on Taiwan Island (Huang and Lin 2010;Liu et al 2011;Oshida et al 2011;Tsai et al 2014). The taxa that dwell at alpine areas in mountainous Taiwan have had particular association with the periodical glaciation events which brought biota from high-latitude regions to this island.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that several factors, such as glacial events and mountain–island isolations, promoted the diversity of endemic species on Taiwan Island (Huang and Lin ; Liu et al. ; Oshida et al. ; Tsai et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation